NK1‐receptor‐expressing paraventricular nucleus neurones modulate daily variation in heart rate and stress‐induced changes in heart rate variability - Feetham, Claire H. (Physiol Rep, 2014)
The paraventricular nucleus of the hypothalamus (PVN) is an established center of cardiovascular control, receiving projections from other nuclei of the hypothalamus such as the dorsomedial hypothalamus and the suprachiasmatic nucleus. The PVN contains a population of “pre‐autonomic neurones” which project to the intermediolateralis of the spinal cord and increase sympathetic activity, blood pressure, and heart rate. These spinally projecting neurones express a number of membrane receptors including GABA and substance P NK1 receptors. Activation of NK1‐expressing neurones increases heart rate, blood pressure, and sympathetic activity. However, their role in the pattern of overall cardiovascular control remains unknown. In this work, we use specific saporin lesion of NK1‐expressing PVN rat neurones with SSP‐SAP and telemetrically measure resting heart rate and heart rate variability (HRV) parameters in response to mild psychological stress. The HRV parameter “low frequency/high frequency ratio” is often used as an indicator of sympathetic activity and is significantly increased with psychological stress in control rats (0.84 ± 0.14 to 2.02 ± 0.15; P < 0.001; n = 3). We find the stress‐induced increase in this parameter to be blunted in the SSP‐SAP‐lesioned rats (0.83 ± 0.09 to 0.93 ± 0.21; P > 0.05; n = 3). We also find a shift in daily variation of heart rate rhythm and conclude that NK1‐expressing PVN neurones are involved with coupling of the cardiovascular system to daily heart rate variation and the sympathetic response to psychological stress.